Recent advances in biosensor for detection of lung cancer biomarkers - Yang, Gaojian; Xiao, Ziqi; Tang, Congli; Deng, Yan; Huang, Hao; He, Ziyu (Biosensors & bioelectronics, 2019)
Lung cancer is primary cancer threatening human life worldwide with the highest mortality rate. The early detection of lung cancer plays a critical role in the early diagnosis and subsequent treatment. However, the conventional methodologies limit the applications due to the low sensitivity, being expensive, and invasive procedure. Tumor markers as biochemical parameters can reflect cancer occurrence and progression, which show sensitivity, convenience, and low cost in developing biosensors, and act as good candidates for fabricating biosensors of detecting lung cancer. This review describes various biosensors (2013-2019) for detection of lung cancer biomarkers. Firstly, the various reported tumor markers of lung cancer are briefly described. Then, the advancements of designing biosensors for sensitive, stable, and selective identification of lung cancer biomarkers are systematically provided, with a specific focus on the main clinical biomarkers such as neuron-specific enolase (NSE), cytokeratin 19 fragment (CYFRA 21-1). Finally, the recent challenges and further opportunities for developing effective biosensors for early diagnosis of lung cancer are discussed. •The function of primary biomarkers of lung cancer are introduced in detail.•The developments of biosensors (2013-2019) for the detection of important lung cancer markers are reviewed.•The challenges of lung cancer in early diagnosis and the two corresponding protocols are enlightened.